S14-1: Building an All-Island Interdisciplinary Consortium for Research on Women in Sport, Exercise, Physical Activity, and Health (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Outlining the development of an all island consortium for research on women in sport, physical activity, exercise, and health can provide a template for other countries to replicate our approach, which ultimately aims to conduct higher quality interdisciplinary research and to prioritise dissemination to influence policy and practice related to girls and women’s engagement in sport, physical activity, and exercise. Project or Policy Description: Work towards developing this consortium commenced in late 2019, with purposeful activity delayed until 2022 for several reasons, including COVID-19. Representatives from higher education institutes (HEIs) across the island of Ireland convened to confirm the need and enthusiasm for this unique approach to sport and exercise science research. In turn, a survey was carried out on the people and projects of women in sport across the island and two focus groups/workshops were delivered with support from Sport Ireland. At this point a leadership group was established in January 2024 to oversee the formalisation of the consortium. Representatives from across the disciplines of sport and exercise science and from HEIs across the island met monthly to debate and finalise the mission, vision, values, and operating format of the consortium. The consortium, titled ‘míde’ launched in January 2025 at an event, which was endorsed and supported by almost 200 attendees from across research, policy, and practice. Scaling up plans for míde are working well, with several ongoing projects and funding successes to date. Conclusions: The mission for míde is to advance interdisciplinary and impactful research about women in sport, exercise, physical activity, and health across the lifespan, generating insights that shape and inform policy, enhance practice, and foster inclusivity and equality for women and girls.